2022
DOI: 10.1080/10717544.2022.2079769
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin-loaded PLGA nanoparticles activate immunogenic cell death and facilitate tumor recruitment in mice with gastric cancer

Abstract: This study aimed to explore the anti-tumor effect of icaritin loading poly (lactic-co-glycolic acid) nanoparticles (refer to PLGA@Icaritin NPs) on gastric cancer (GC) cells. Transmission Electron Microscope (TEM), size distribution, zeta potential, drug-loading capability, and other physicochemical characteristics of PLGA@Icaritin NPs were carried out. Furthermore, flow cytometry, confocal laser scanning microscope (CLSM), Cell Counting Kit-8 (CCK-8), Transwell, Elisa assay and Balb/c mice were applied to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…We speculate that icaritin-induced senescence may be related to the above factors, and the increased expression of the DNA damage marker protein γ-H2AX further supports our speculation. ROS is closely associated with DNA damage, cell senescence, and other cellular damages (Maciel-Baron et al, 2018;Xiao et al, 2022). Several studies have shown that icaritin can promote ROS production in tumor cells, and our flow cytometry results showing that icaritin can enhance ROS levels in nasopharyngeal carcinoma cells are consistent with the findings of these studies (Li et al, 2016;Chen et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…We speculate that icaritin-induced senescence may be related to the above factors, and the increased expression of the DNA damage marker protein γ-H2AX further supports our speculation. ROS is closely associated with DNA damage, cell senescence, and other cellular damages (Maciel-Baron et al, 2018;Xiao et al, 2022). Several studies have shown that icaritin can promote ROS production in tumor cells, and our flow cytometry results showing that icaritin can enhance ROS levels in nasopharyngeal carcinoma cells are consistent with the findings of these studies (Li et al, 2016;Chen et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The proposed QA/QC characteristics allow the new method to be considered an original addition to the work that uses metal nanoparticles to solve analytical and pharmaceutical problems [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulated evidence indicates that the level of ICD signaling was correlated with the response to treatment and prognosis of patients with GC [ 39 , 40 , 41 ]. However, most previous studies focused on a single ICD-related gene, which could cause limited prognostic and predictive power, and the overall effects exerted by the ICD-related genes have not yet been fully illuminated in GC.…”
Section: Discussionmentioning
confidence: 99%